Adapting To The New Normal: Assessing Levers Of Control Implementation In Indonesian Organizations Post-COVID - Latifah Atela Anwar (Al-Makki Publisher, 2024)
This systematic literature review investigates the application of the Four Levers of Control (4LOC) framework in Indonesian organizations post-COVID-19. The research method involved a systematic search of electronic databases and analysis of relevant literature. Major findings indicate that effective implementation of the 4LOC framework contributes to organizational resilience, performance improvement, and competitive advantage across various sectors. Cultural factors, leadership styles, and strategic alignment emerge as critical determinants of success. The study underscores the versatility and effectiveness of the 4LOC framework in navigating challenges posed by dynamic environments. Conclusions highlight the importance of adaptive strategies, cultural sensitivity, and integrated control systems in driving sustainable growth and organizational success in Indonesia. Results indicate that LoC implementation has positively impacted organizational performance across sectors such as hospitality, start-ups, state-owned enterprises, government organizations, manufacturing, and the service industry. Notably, effective utilization of belief systems, boundary systems, diagnostic control systems, and interactive control systems has been instrumental in fostering innovation, resilience, and strategic alignment. These findings underscore the importance of robust management control systems in achieving organizational objectives and navigating uncertainties. The review concludes by recommending further research to explore longitudinal effects, contextual influences, and the role of emerging technologies in enhancing LoC implementation.